Gender Justice in Ethiopia: Governance Gaps and Policy Effectiveness - Kebede, Geneti Feyissa (European Scientific Journal, ESJ, 2026)
Gender justice is a key indicator of a nation’s declared commitment to inclusive development. Building on this premise, the current study assesses the performance of gender justice policies in Ethiopia using a mixed-methods approach. Primary data were collected from 1,582 participants (90.92% response rate) using self-administered questionnaires as well as nine (9) interviews. Survey participants were chosen through simple random sampling, whereas interviewees were public officials chosen purposely. Furthermore, multi-year nationwide secondary data were obtained from federal institutions. The findings indicate that women’s self-readiness and institutional support (B = 6.69), governing capacity (B = 3.11), policy quality (B = 2.54), transnational engagement (B = 1.60), and sociocultural norms (B = 1.10) have statistically significant positive effects on gender justice outcomes (R² = 0.71). These unstandardized coefficients represent the expected change in gender policy effectiveness for a one-unit increase in each predictor. Despite these contributions, the overall status of gender justice remains moderate and uneven across governance levels, with performance declining from federal to local levels. Persistent barriers—including inconsistent political commitment, institutional capacity gaps, and entrenched sociocultural norms such as glass ceilings and related structural constraints—continue to limit progress. The study concludes that while Ethiopia has made notable advances, outcomes fall short of policy ambitions. It recommends institutionalizing gender justice performance benchmarking, strengthening institutional capacity through enforceable implementation frameworks, converting political commitment into measurable accountability, improving policy quality through mandatory feasibility assessments, investing in women’s leadership incubation and empowerment, implementing comprehensive sociocultural transformation strategies, and strengthening transnational engagement while ensuring domestic ownership.